Tetanus and botulinum toxin use: report of a case - Alvis-Peña, Diego J. (2020)
Tetanus is a condition affecting the central nervous system which is characterized by muscle spasms caused by toxins from Clostridium tetani, an anaerobe bacillus which is usually found on soil and whose spores may survive in the environment and lead to infection when contaminating open wounds. The objective of this case report is to review on the basic characteristics of this condition, focusing on functional improvement with the administration of type A botulinum toxin for generalized spasticity and lockjaw (trismus). We present the case of an 81-year-old woman with generalized tetanus and lockjaw after she suffered a head injury, she fell and hurt her head, with no loss of consciousness; and that was 15 days before admission. During her hospital stay she was managed by a multidisciplinary team. The patient did well, and she is currently being followed-up in the outpatient clinic.